2017
DOI: 10.1002/lary.26853
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes of KTP laser surgery versus radiation for T1 glottic carcinoma

Abstract: 4. Laryngoscope, 128:1052-1056, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Short treatment duration, no risk of irradiation‐induced malignancy, the possibility of repetitive applications, and more remaining salvage options favor laser‐based TLM compared to RT especially in vocal fold leukoplakia . In a recent retrospective study, oncological outcome after TLM‐KTP and RT appears to be comparable in T1 glottic squamous cell carcinoma . In a small cohort of 20 patients with recurrent glottic cancer (rT1‐rT2), TLM‐KTP was even used as a salvage measure in failed RT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short treatment duration, no risk of irradiation‐induced malignancy, the possibility of repetitive applications, and more remaining salvage options favor laser‐based TLM compared to RT especially in vocal fold leukoplakia . In a recent retrospective study, oncological outcome after TLM‐KTP and RT appears to be comparable in T1 glottic squamous cell carcinoma . In a small cohort of 20 patients with recurrent glottic cancer (rT1‐rT2), TLM‐KTP was even used as a salvage measure in failed RT .…”
Section: Discussionmentioning
confidence: 99%
“…42 In a recent retrospective study, oncological outcome after TLM-KTP and RT appears to be comparable in T1 glottic squamous cell carcinoma. 43 In a small cohort of 20 patients with recurrent glottic cancer (rT1-rT2), TLM-KTP was even used as a salvage measure in failed RT. 44 Although 80% of the treated patients were reported free of disease after 2 years, the concept of TLM-KTP should currently only be applied within GCP-ICH-conform clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…A, Well differentiated; B, moderately differentiated; C, poorly or undifferentiated; and D, differentiation unknown on <100 patients. [21][22][23][24] In a large meta-analysis that included 562 participants treated with laser surgery and 706 participants treated with radiotherapy, the pooled analysis showed that laser surgery significantly improved the overall survival of patients with T1 glottic carcinoma group. 25 In the current study, surgery yielded better survival than radiotherapy in patients with T1a stage glottis SCC, but not T1b, T1 not specified, or T2 stages.…”
Section: F I G U R Ementioning
confidence: 99%
“…There are multiple options described in the literature for treating glottic carcinoma, and these consist of open surgery, TLM, or radiation. 1 There has been a transition from external surgery to endoscopic laser microsurgical techniques which have been possible mainly due to a landmark study by Professor Wolfgang Steiner (1993) and the European Laryngological Society's (ELS) classification scheme (2000). 5 TLM is the mainstay of treatment for early glottic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Glottic carcinoma is the most common subtype. 1 Treatment options include laser treatment, radiation, partial or total laryngectomy and in recent years, transoral robotic surgery.…”
Section: Introductionmentioning
confidence: 99%